Psychological and Psychiatric Comorbidities in Youth with Serious Physical Illness - Sohail Nibras; Rachel Kentor; Yasir Masood; Karin Price; Nicole M. Schneider; Rachel B. Tenenbaum; Chadi Calarge (MDPI AG, 2022)
An estimated one in six children in the United States suffers from a mental disorder, including mood, anxiety, or behavioral disorders. This rate is even higher in children with chronic medical illness. This manuscript provides a concise review of the symptoms that comprise mental conditions often observed in children with chronic illness or at the end of life. It further provides some guidance to help clinicians distinguish normative from pathological presentations. Evidence-based psychotherapy interventions, potentially applicable to the acute inpatient setting, are briefly summarized. Broad recommendations are made regarding both psychotherapeutic as well as pharmacotherapeutic interventions, with a review of common or serious medication side effects. Finally, delirium recognition and management are summarized.